Pelaksaan Perjanjian Terapeutik Antara Pasien dengan Rumah Sakit Jiwa Jambi - Supeno Supeno; Fachruddin Razi; Fauty Intan Faradila (Universitas Batanghari Jambi, 2021)
Generally an agreement is an agreement made by both parties or more about something they agree to, and in the agreement contains the rights and obligations of each party. In this study formulates how the implementation of the agreement in a mental hospital because the patient has a psychiatric disorder so incapable to do the agreement so represented by the family / guardian of the patient and the problem of what happens about rights or obligations that are not obtained or not implemented. when the patient is incapable and competent to approve medical measures. Whether or not a patient with a psychiatric disorder consents, it also affects the obligations of the guardian or the person in charge of the patient, because the guardian is the person in charge of the patient, after agreeing that both parties are bound by the therapeutic agreement. But in the implementation of the therapeutic agreement can not always be implemented properly, the purpose of this study is to find out how the contents of the agreement between the hospital and the mental hospital patient, what problems occur in the implementation of the agreement between the mental hospital and the patient and how to solve the problems that occur between the hospital and the patient of jambi mental hospital. The results showed that the hospital and patients are bound in a standard agreement in which there are each right and obligation of both parties, the problem that occurs is the negative treatment of medical personnel to mental hospital patients, negligence done by the patient's family to the hospital, the resolution of problems that occur solved by musywarah and the hospital directly visit the family who abandoned his family in jambi mental hospital.